2019
DOI: 10.1186/s12885-019-5727-9
|View full text |Cite
|
Sign up to set email alerts
|

ERO1α is a novel endogenous marker of hypoxia in human cancer cell lines

Abstract: Background Hypoxia is an important factor that contributes to tumour aggressiveness and correlates with poor prognosis and resistance to conventional therapy. Therefore, identifying hypoxic environments within tumours is extremely useful for understanding cancer biology and developing novel therapeutic strategies. Several studies have suggested that carbonic anhydrase 9 (CA9) is a reliable biomarker of hypoxia and a potential therapeutic target, while pimonidazole has been identified as an exogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
(43 reference statements)
3
6
0
Order By: Relevance
“…Moreover, stage Ib/ II fTME GC showed the highest mean hypoxia score and lowest RCT response score across all the subgroups in the pooled cohort (Figure 4B). We further validated our findings through a novel endogenous hypoxia marker-ERO1A (28) and observed that the TMEscore was positively correlated with the mRNA expression of ERO1A in all the cohorts (Figure 4C). Similar results were found for the mRNA expression of TS (Figure 4C)-the target of FU and an indicator of poor CT outcomespotentially in association with upregulation by hypoxia (21,29).…”
Section: Tumor Microenvironment Status and Hypoxiasupporting
confidence: 70%
“…Moreover, stage Ib/ II fTME GC showed the highest mean hypoxia score and lowest RCT response score across all the subgroups in the pooled cohort (Figure 4B). We further validated our findings through a novel endogenous hypoxia marker-ERO1A (28) and observed that the TMEscore was positively correlated with the mRNA expression of ERO1A in all the cohorts (Figure 4C). Similar results were found for the mRNA expression of TS (Figure 4C)-the target of FU and an indicator of poor CT outcomespotentially in association with upregulation by hypoxia (21,29).…”
Section: Tumor Microenvironment Status and Hypoxiasupporting
confidence: 70%
“…Importantly, Ero 1α levels have been found correlated to PD-L1 expression in vitro and in vivo, suggesting Ero 1α as a potential target in cancer immunotherapy (20). Consistently with these evidences, Ero 1α has been found correlated with bad prognosis in different types of cancers, such as breast, pancreatic, cervical and gastric cancers (21)(22)(23)(24).…”
Section: Introductionsupporting
confidence: 52%
“…In particular, hypoxia is a frequent condition during tumorigenesis and a key feature of the tumor microenvironment (14). Ero 1α has been proposed as a marker of hypoxia in various kinds of cancers as it is induced by low-oxygenic environments via the hypoxiainducible factor 1 (HIF-1) (15). It also controls mRNA levels and folding of vascular endothelial growth factor A (VEGF-A), a molecule essential for neoangiogenesis (16).…”
Section: Introductionmentioning
confidence: 99%
“…In order to verify the hypoxia difference between PNI-positive and PNI-negative tumors, we detected the protein expression of ERO1A, a novel endogenous marker of hypoxia in cancer (29), in 49 GC tissues of the AHJU cohort (Figure 5C). The ERO1Apositive rate was significantly lower in PNI-positive tumors than in PNI-negative tumors (p = 0.015; Figure 5D).…”
Section: Pni-associated Tme May Determine Chemotherapy Responsementioning
confidence: 99%